FSH priming and hormonal modulation of oocyte competence in in vitro maturation for infertility treatment: a systematic review and meta-analysis - Lin, Krystal Baysan; Chien, Yungchen; Hou, Jung-Hsiu; Wu, Yen-Chen; Lin, Ping Lun; Chien, Li-Ting; Chen, Chi-Huang (Frontiers in Endocrinology, 2025)
BackgroundDoes follicle-stimulating hormone priming improve reproductive outcomes in women undergoing in vitro maturation treatment for infertility?Follicle-stimulating hormone (FSH) is a key endocrine regulator of oocyte folliculogenesis and is crucial for granulosa-oocyte communication and cytoplasmic maturation. In vitro maturation (IVM) offers a lower risk when compared with conventional in vitro fertilization ovarian stimulation; however, widespread clinical adoption is limited by variable success rates and protocol heterogeneity. In regard to optimization strategies, FSH priming has been proposed to enhance oocyte competence, but its impact remains debatable.ObjectiveTo evaluate the effects of FSH priming on oocyte maturation and reproductive potential in IVM cycles for infertile women.MethodsEmploying PRISMA guidelines, we systematically searched PubMed, Cochrane Library, Embase, and Web of Science for randomized controlled trials comparing FSH-primed versus non-primed IVM cycles in infertile women. The primary outcome was oocyte maturation rate, whereas secondary outcomes included fertilization rate, cleavage rate, pregnancy rate, and implantation rate. Data pooled used random-effects models, with heterogeneity assessed by I2 statistic.ResultsSix randomized controlled trials comprising of 497 women were analyzed. FSH priming was associated with a statistically significant increase in oocyte maturation rate [OR 1.24(95% CI, 1.05-1.45)] when compared with the non-stimulated group. However, pooled analysis showed no significant differences in fertilization rate or clinical pregnancy rate between groups.ConclusionFSH priming has been shown to enhance oocyte maturation rate in in vitro maturation cycles. However, current evidence shows that gonadotropin does not significantly improve fertilization or pregnancy outcomes.